2011
DOI: 10.1002/anie.201100735
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Chain Growth by Formyl Insertion on Rhodium and Cobalt Catalysts in Syngas Conversion

Abstract: Syngas (CO/H 2 ) produced from coal, natural gas, or biomass has attracted much attention as alternative to petroleumderived fuels and chemicals. Syngas can be selectively converted to oxygenates, such as alcohols, aldehydes, and carboxylic acids, or hydrocarbons by Fischer-Tropsch synthesis (FTS). [1] Industrially, rhodium- [2] and cobalt-based [3] catalysts are often used for production of C 2 oxygenates and hydrocarbons. Despite numerous studies, the exact mechanism remains in debate, and represents a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 35 publications
7
92
1
3
Order By: Relevance
“…Previous theoretical studies reported that C−O bond cleavage shows strong structural effects, which intensively requires a double stepedge site with a high-lying d-state; 18,20 the barrier for C−O bond cleavage is obviously higher than that for C−C cleavage. 47,48 This indicates that C−O bond cleavage requires a higher d-band-energy-state of active metal than C−C bond breaking. As a result, based on the desirable modulation of the metal d-band center position to a moderate energy state, the Ru−Ni interfacial sites as active sites substitute the original Ni surface defects, resulting in the inhibition of C−O breaking and the promotion of C−C bond cleavage.…”
Section: Chemistry Of Materialsmentioning
confidence: 98%
“…Previous theoretical studies reported that C−O bond cleavage shows strong structural effects, which intensively requires a double stepedge site with a high-lying d-state; 18,20 the barrier for C−O bond cleavage is obviously higher than that for C−C cleavage. 47,48 This indicates that C−O bond cleavage requires a higher d-band-energy-state of active metal than C−C bond breaking. As a result, based on the desirable modulation of the metal d-band center position to a moderate energy state, the Ru−Ni interfacial sites as active sites substitute the original Ni surface defects, resulting in the inhibition of C−O breaking and the promotion of C−C bond cleavage.…”
Section: Chemistry Of Materialsmentioning
confidence: 98%
“…The first layer is , the second layer , the third layer and the forth layer of chain propagation and termination is crucial for the production of desired products. Although it is difficult to simulate the elementary steps involving large molecules on the catalyst surface due to the limitation of current computational capacity, some theoretical efforts [36,37,116,119,120,143] have been devoted to this field concerning the formation of C 2 and C 3 . Hu and coworker have investigated all the possible reaction pathways for C 1 ?…”
Section: Chain Growthmentioning
confidence: 99%
“…It is well known that syngas mainly contains CO and H 2 along with a small amount of CO 2 [52], meanwhile, the extensive studies about C 2 H 5 OH formation form syngas on Rh-based catalysts have been reported [7,9,11,15], in which only CO hydrogenation to form C 2 H 5 OH are considered. On the other hand, when CO 2 hydrogenation is considered to form C 2 H 5 OH, on the basis of the number of O atom in C 2 H 5 OH, we think CO 2 firstly needs to be converted to CO, then, CO hydrogenates to product C 2 H 5 OH.…”
Section: Resultsmentioning
confidence: 99%
“…For C 2 oxygenates formation, the studies on Rh and Co catalysts by Zhao et al [15] found that CHO insertion into CH x (x = 1-3) is superior and/or competitive to CO insertion and carbene coupling for chain growth; moreover, Choi and Liu [7] have found that CH 3 is the most favored monomer on Rh(1 1 1) surface among all CH x (x = 1-3) species, meanwhile, the productivity and selectivity of C 2 H 5 OH is controlled by CH 3 hydrogenation to CH 4 formation and CO insertion into CH 3 to C 2 oxygenates. In this study, CH 3 are the most favored monomer formed by syngas on Cu(1 0 0) surface, in order to illustrate C 2 oxygenates formation, we further investigate CO insertion into CH 3 , CHO insertion into CH 3 , as well as CH 3 hydrogenation, dissociation and coupling on Cu(1 0 0) surface.…”
Section: Oxygenates Formationmentioning
confidence: 99%
See 1 more Smart Citation